2014
DOI: 10.1080/07448481.2014.960423
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Issues Among College Students: Who Gets Referred for Psychopharmacology Evaluation?

Abstract: Depression, anxiety, and ADHD are common among students referred by college counseling centers for medication evaluation and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Additionally, there is substantial research that demonstrates that harmful and hazardous alcohol consumption also contributes to arange of mental health problems and disorders including depression, anxiety, and stress or psychological distress [12,13]. Studies in Europe, the USA and Australia haveshown a high prevalence of alcohol use disorders, alcohol dependence, stress, anxiety,eating disorders and depression among university students [1417] compared to their non-university peers [18]. The association between alcohol and mental health is bi-directional with studies suggesting that individuals who are predisposed to harmfulalcohol consumption are prone to episodes of stress, depression, and anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is substantial research that demonstrates that harmful and hazardous alcohol consumption also contributes to arange of mental health problems and disorders including depression, anxiety, and stress or psychological distress [12,13]. Studies in Europe, the USA and Australia haveshown a high prevalence of alcohol use disorders, alcohol dependence, stress, anxiety,eating disorders and depression among university students [1417] compared to their non-university peers [18]. The association between alcohol and mental health is bi-directional with studies suggesting that individuals who are predisposed to harmfulalcohol consumption are prone to episodes of stress, depression, and anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…3 Epidemiological evidence shows that depression and anxiety are the most common psychiatric problems in college students. 4 Youth who experience anxiety and depression have a significantly increased risk of negative physical and psychosocial outcomes, such as academic difficulties, poor interpersonal relationships, low selfesteem and suicide. 5 6 In the last decade, the use of electronic media devices has dramatically increased among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol related harm is a major public health problem (Bell & Britton, 2014;WHO, 2012). Studies in Europe, the USA and Australia have shown a high prevalence of alcohol use disorders, alcohol dependence, stress, anxiety, eating disorders and depression among university students (Kirsch, Doerfler & Truong, 2014;Said, Kypri & Bowman, 2013;Slutske, 2005;Stallman, 2010) compared to their non-university peers (Cvetkovski, Reavley & Jorm, 2012). Studies of the association between alcohol and mental health suggest that individuals with harmful alcohol consumption are more likely to report stress, depression, and anxiety (Pereira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%